EDUCATION ON THE BENEFITS OF LEMONGRASS (cymbopogon citratus) LEAF EXTRACT AS A ANTIBACTERIAL MOUTHWASH - Fahdi, Firdaus; Sari, Herviani; Sembiring, Bunga Mari (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Dental and oral health problems are a serious problem. Even though it looks simple, maintaining oral and dental hygiene is important to maintain quality of life. Dental caries is the main cause of dental problems, this occurs due to an individual's lack of knowledge in maintaining the cleanliness of their teeth and mouth. Using lemongrass as an alternative mouthwash is another option in an effort to maintain oral hygiene. This service activity was carried out at Sembiring Deli Tua Hospital targeting participants from children to adults. Activities are carried out in three stages, namely the preparation stage, implementation stage and feedback. After participating in the service activities, it was discovered that there was an increase in participants' understanding and knowledge in maintaining oral and dental hygiene.